Stained glass windows - Ghosh, Ayan (2023)
Frederick W. Stevens was primarily influenced by Gothic architecture, and it is in Gothic that most of his projects were executed. Within the Gothic genre, Stevens had a particular liking for Venetian Gothic, which originated in Italy in the twelfth century. Inspired by Venetian Gothic, Stevens used stained-glass windows extensively throughout the BMC building.